A new sibling species of Halyzia straminea (Hope) (Coleoptera: Coccinellidae: Halyziini) from the Indian subcontinent - Poorani, J.; Booth, R. G. (Zootaxa, 2006)
Halyzia dejavu sp. n., a sibling species of Halyzia straminea (Hope), is described from India and Nepal. The distinguishing characters, including the male and female genitalia, are described in detail and illustrated in comparison with H. straminea.